Analisis Perubahan Penggunaan Lahan Di Kecamatan Grogol Kabupaten Sukoharjo Tahun 2005 Dan Tahun 2013 - Mayasari, Tantri; , Dr. H. Kuswaji Dwi Priyono, M.Si; , Ir. H. Taryono, M.Si (2015)
This research was conducted in Grogol, Central Java Province. This study aims to: (1) analyzing the distribution of landuse change in Grogol between 2005 and 2013 and (2) analyze factors that influence changes in landuse in Grogol. The method used in this study were: (1) using secondary data from landuse maps of 2005 and 2013 as well as statistical data relating to changes in landuse in Grogol and (2) analysis of maps using the method used to determine the direction komperasi landuse suitability. The results obtained in this study is the change in landuse of high and low with the factors affecting the socio-economic facilities, population density and population growth. Changes in landuse was found in the village area of 14.03 ha Madegondo (5.51%) and the Village Cemani measuring 7.26 ha (0.85%) and low landuse change are in the village area of 5.88 ha Kadokan ( 1.91%), Village Pandeyan area of 9.08 ha (2.95%), and the village of Manang area of 6.029 ha (1.96%) of the total area of landuse change in Grogol area of 308.12 ha. From the results of the classification of the factors that influence in other districts Grogol with the District downtown Surakarta as the result of the pattern of distribution of landuse direction from the center to the north of the center Grogol subdistrict Surakarta as the population as a principal temporary labor so that development growth unchanged significantly.